Effect of Intravenous Lignocaine Infusion on Intraoperative Hemodynamic Stability in Patients Undergoing Laparoscopic Cholecystectomy: A Randomized Controlled Trial - Dr. Shilpa Meharra; Dr Shiva Tanwar; Dr Vishal Devra; Dr. Mohd Yunus Khilji; Dr. Kanta Bhati; Dr. Sonali Dhawan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Laparoscopic cholecystectomy, though minimally invasive, is associated with significant hemodynamic fluctuations during laryngoscopy, pneumoperitoneum, and extubation. Intravenous lignocaine, an amide local anesthetic with membrane-stabilizing properties, has been suggested as an adjunct for blunting stress responses. Objective: To evaluate the efficacy of intravenous lignocaine infusion in attenuating intraoperative hemodynamic responses in patients undergoing laparoscopic cholecystectomy. Methods: In this prospective, double-blind, randomized controlled trial, 70 ASA I–II patients were divided into two groups (n=35 each). Group L received lignocaine (1.5 mg/kg bolus + 2 mg/kg/hr infusion), and Group C received saline. Hemodynamic parameters (SBP, DBP, MAP, HR, SpO₂) were monitored perioperatively. Results: Lignocaine significantly reduced systolic and mean arterial pressures at intubation and extubation (p<0.01). MAP was consistently lower intraoperatively in Group L. HR and SpO₂ remained comparable across groups. Laparoscopic cholecystectomy, Intravenous lignocaine, Hemodynamic stability, Intubation, Pneumoperitoneum. Conclusion: Intravenous lignocaine infusion attenuates intraoperative hemodynamic responses during laparoscopic cholecystectomy, supporting its use as a safe and effective adjuvant for perioperative stability.